KID syndrome patient with toe walking: A case report - EROL, BÜLENT; KARADAĞ SAYGI, NAİME EVRİM (INFORMA HEALTHCARE, 2009)
Objective: To report on a 10-year-old boy with KID syndrome who presented with a new onset unilateral toe walking. Method: This patient's equinus contracture was evaluated clinically. The patient underwent to surgical lengthening of Achilles tendon. After the surgery, the patient was placed in a short-leg walking cast for 6 weeks and then received a rehabilitation programme involving stretching exercises. Results: Successful heel-to-toe gait was achieved in 3 weeks following surgery and rehabilitation. Conclusion: Surgical intervention and postsurgical rehabilitation may be indicated for children who present with toe walking attributed to contracture in the Achilles tendon.
Keywords: KID syndrome; toe-walking; Achilles tendon lengthening